2016
DOI: 10.1097/md.0000000000002394
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophilic Cholangitis—A Challenging Diagnosis of Benign Biliary Stricture

Abstract: When confronting a biliary stricture, both benign and malignant etiologies must be carefully considered as a variety of benign biliary strictures can masquerade as hilar cholangiocarcinoma (CCA). Therefore, patients could undergo a major surgery despite the possibility of a benign biliary disease. Approximately 15% to 24% of patients undergoing surgical resection for suspected biliary malignancy will have benign pathology. Eosinophilic cholangitis (EC) is a rare benign disorder of the biliary tract, which can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 14 publications
0
22
0
Order By: Relevance
“…Eosinophilic Cholangitis (EC) is a rare, benign disease of transmural eosinophilic infiltration of the biliary tree leading to stricture formation and obstruction [1,3]. Most cases present as a focal process within the biliary system, although there have been a few reported cases of concomitant disease in the kidneys, ureters and pericardium [4].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Eosinophilic Cholangitis (EC) is a rare, benign disease of transmural eosinophilic infiltration of the biliary tree leading to stricture formation and obstruction [1,3]. Most cases present as a focal process within the biliary system, although there have been a few reported cases of concomitant disease in the kidneys, ureters and pericardium [4].…”
Section: Discussionmentioning
confidence: 99%
“…in 1985 who reported a case of a thickened gallbladder wall and stenosis of intrahepatic bile ducts with eosinophilic infiltration in the cystic duct, gallbladder, lymph nodes and bone marrow, consistent with EC [4,5]. EC is hypothesized to originate from increased IgE, IL-5 levels leading to diffuse eosinophilic infiltration of the biliary system with TGF-ß produced by eosinophils leading to fibrosis and subsequent stricture formation of the biliary tract [1,6,7]. While the inciting cause is unknown, EC has also been proposed as a possible extension of cholecystitis secondary to infections caused by Enterobacter aerogenes or Candida albicans [8].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…EC has been first described in 1985 by Butler et al, since then, a total of 35 patients have been reported (details in Table ). We provide additional five cases of EC, which is the largest single patient series reported.…”
Section: Introductionmentioning
confidence: 99%